2007
DOI: 10.1038/sj.npp.1301594
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 Receptor Antagonism Promotes Active Stress Coping Via Enhanced Septal 5-HT Transmission

Abstract: Antagonists of the substance P (SP) preferring neurokinin 1 receptor (NK1R) represent a promising novel class of drugs for the treatment of stress-related disorders such as depression and anxiety disorders; however, the involved neuronal pathways releasing SP in response to stressors are ill defined. By using in vivo microdialysis in combination with a highly sensitive and selective radioimmunoassay we found that exposure to forced swim stress increased SP release in the rat lateral septum (LS), a key area in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 79 publications
3
50
0
2
Order By: Relevance
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 5-HT transmission in the mpFC is likely to engage GABA in the amygdala in stressful situations in order to determine coping outcomes. Here, using mice, it was attempted to assess whether amygdalar GABA regulation by prefrontal cortical 5-HT is a common neural substrate involved in processing stressful experiences and in determining active or passive coping behavior during forced swimming (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). In particular, it was investigated whether 5-HT in prefrontal cortex is involved in brain response to uncontrollable stress through its modulating action on GABA in amygdala and whether these brain areas are part of a neural system necessary for the implementation of adaptive coping strategies.…”
Section: Introductionmentioning
confidence: 99%
“…That is, in line with the present observations, NK 1 receptors are 'upstream' of 5-HT 1A autoreceptors. Interestingly, by analogy to lateral septum (Ebner et al, 2008), frontocortical perfusion of substance P suppressed local release of 5-HT in mice, an effect blocked by GR205171 and absent in mice lacking NK 1 receptors (Guiard et al, 2007). Thus, NK 1 antagonists conceivably also enhance SSRI-induced increase in 5-HT levels by actions in the FCX and other structures innervated by the DRN.…”
Section: Discussion Potentiation By Gr205171 Of the Influence Of Citamentioning
confidence: 99%
“…Possible Involvement of Gabaergic, Glutatamergic, and Adrenergic Mechanisms NK 1 receptors have been identified on GABAergic neurones surrounding 5-HT cell bodies in the DRN, and studies in the septum and cortex suggest that NK 1 receptor antagonists may indirectly excite serotonergic neurones via a reduction of inhibitory GABAergic tone (Sloviter et al, 2001;Ma and Bleasdale, 2002;Stacey et al, 2002;Szeidemann et al, 1995;Ebner et al, 2008). This would enhance their responsiveness to SSRIs, by analogy to GABA B antagonists (Millan, 2006;Cremers et al, 2007).…”
Section: Discussion Potentiation By Gr205171 Of the Influence Of Citamentioning
confidence: 99%
See 1 more Smart Citation